The Summons - Grisham, John (India Arrow, 2002)
Ray Atlee and his brother, Forrest, receive a letter from their father, a reclusive, retired judge, instructing them to return home to Clanton, Mississippi, to discuss his estate, but the judge dies before his sons arrive, leaving behind a secret known only to Ray.
Keywords: Mississippi -- Inheritance and succession -- Fathers and sons